A Comparative Study: Tinkercad-Assisted PBL And STAD Cooperative on Learning Activity and Outcomes of Electrical Materials - Marcelinus Widananta; Joko Sulianto; Joko Siswanto (International Journal of Elementary Education, 2025)
Student activity and learning outcomes in science lessons on electricity show less than optimal results, so a learning model is needed that can stimulate students to be more active, which will ultimately affect their learning outcomes.  This study aims to test and determine the differences between the use of the STAD cooperative model and the Tinkercad media-assisted PBL model on student learning outcomes and activity. This study uses a quantitative approach with a quasi-experimental design: Posttest-only design with nonequivalent groups. The research subjects included seventh-grade students. Research data were collected through tests, observations, and questionnaires. Data analysis used regression tests, independent t-tests, and completeness tests. The results showed that students who received the PBL learning model assisted by Tinkercad media (experimental class) had higher and significantly higher average activity and learning outcomes than students who received the STAD cooperative learning model (control class). In the experimental class, student activity had a positive and significant effect on affective learning outcomes (R-square = 40% (moderate)), but activity on knowledge and skill aspects had a low effect (R-square = 6%-10%) after learning. Meanwhile, in the control group, activity did not have a significant effect on student learning outcomes (R-square = <2%). Therefore, the application of the PBL model assisted by Tinkercad media can make science lessons on electricity more meaningful and easier to understand than the STAD cooperative model.